Sleep [large type] - Jones, Honor (Random House Large Print Publishing, 2025)
"From a dazzling new talent, the story of a newly divorced young mother forced to reckon with the secrets of her own childhood when she brings her daughters back to the opulent house where she was raised. Every parent exists inside of two families simultaneously - the one she was born into, and the one she has made. Ten-year-old Margaret hides beneath a blackberry bush in her family's verdant backyard while her brother hunts for her in a game of flashlight tag. Hers is a childhood of sunlit swimming pools and Saturday morning pancakes and a devoted best friend, but her family life requires careful maintenance. Her mother can be as brittle and exacting as she is loving, and her father and brother assume familiar, if uncomfortable, models of masculinity. Then late one summer, everything changes. After a series of confusing transgressions, the simple pleasures of suburban life, and of girlhood, slip away. Twenty-five years later, Margaret hides under her bed, waiting for her young daughters to find her in a game of hide and seek. She's newly divorced and navigating her life as a co-parent, while discovering the pleasures of a new lover. But some part of her is still under the blackberry bush, punched out of time. Called upon to be a mother to her daughters, and a daughter to her mother, she must reckon with the echoes and refractions between the past and the present, what it means to make a child feel safe, and how much of our lives are our own, alone. Warm and generous, unflinchingly human, and ultimately joyful and empowering, SLEEP is about the cycles of motherhood and childhood, the cost of secrets and the burden of love, and what's on the other side of silence: the world, rich in possibility"--